In quest of empowerment : the Grameen Bank impact on women's power and status - Mizan, Ainon Nahar (University Press, 1994)
Impact on socio-economic and political status of women in Bangladesh; study of two villages, Dewannagar in Hathazari and Hetalia in Patuakhali districts.